2021
DOI: 10.1093/infdis/jiab108
|View full text |Cite
|
Sign up to set email alerts
|

The Activin/Follistatin Axis Is Severely Deregulated in COVID-19 and Independently Associated With In-Hospital Mortality

Abstract: Background Activins are members of the TGFβ-superfamily implicated in the pathogenesis of several immuno-inflammatory disorders. Based on our previous studies demonstrating that over-expression of Activin-A in murine lung causes pathology sharing key features of COVID-19, we hypothesized that Activins and their natural inhibitor Follistatin might be particularly relevant to COVID-19 pathophysiology. Methods Activin-A, Activin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…A study limitation is represented by the relatively small number of patients of I st wave in comparison to II nd wave. Further studies need to confirm our findings as a recent work documents NLR predictive value on both I st and II nd waves ( 21 ). However, at the state of the art, there is not a clear consensus on the role of such drugs, frequently used friendly without medical supervision ( 22 ) and on their impact on COVID-19 patients.…”
Section: Discussionsupporting
confidence: 72%
“…A study limitation is represented by the relatively small number of patients of I st wave in comparison to II nd wave. Further studies need to confirm our findings as a recent work documents NLR predictive value on both I st and II nd waves ( 21 ). However, at the state of the art, there is not a clear consensus on the role of such drugs, frequently used friendly without medical supervision ( 22 ) and on their impact on COVID-19 patients.…”
Section: Discussionsupporting
confidence: 72%
“…A study looking at serum samples of patients with severe, active COVID-19 infections found that Activin A, Activin B, and follistatin were all upregulated during the time when COVID-19 patients tended to deteriorate [21]. In a COVID-19 study de ning Acute Respiratory Distress Syndrome (ARDS), cytokine storms were observed in patients with severe COVID-19 symptoms [22].…”
Section: Introductionmentioning
confidence: 99%
“…While we were preparing our manuscript, another manuscript appeared similarly demonstrating activin A was disregulated in COVID-19 patients ( 11 ). The findings in the present manuscript are in agreement with that paper.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated sera from these patients after randomization and prior to therapy, to determine baseline activin A, activin B, FLRG, and PAI-1 levels, and correlated these to baseline clinical and laboratory variables and important disease outcomes. While we were preparing the manuscript, another manuscript appeared demonstrating activin A and activin B are elevated in COVID-19 patients ( 11 ). Our paper is consistent with findings in that manuscript, and goes further in demonstrating mechanism, additional clinical correlations, and providing a preclinical intervention study that helps to derisk this potential treatment approach.…”
Section: Introductionmentioning
confidence: 99%